1995
DOI: 10.1148/radiology.195.3.7753984
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic lesions suggestive of radial scars: microscopic findings in 40 cases.

Abstract: Because of the association of radial scars with borderline and malignant lesions, a spiculated lesion suggestive of a radial scar found at mammography must always be surgically removed. The surgeon and pathologist must be aware of the mammographic aspects of radial scar, however, to avert excessive surgery, because all cancers in this study had a good prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 0 publications
1
37
0
4
Order By: Relevance
“…To add to the diagnostic difficulties posed by radial scars, they cannot be distinguished from spiculate cancers on mammography. Frouge et al 8 assessed 40 cases (20 radial scars and 20 carcinomas) exhibiting at least three of the Tabar and Dean criteria. The authors were unable to differentiate between the mammographic appearances of the radial scars and the cancers.…”
Section: Discussionmentioning
confidence: 99%
“…To add to the diagnostic difficulties posed by radial scars, they cannot be distinguished from spiculate cancers on mammography. Frouge et al 8 assessed 40 cases (20 radial scars and 20 carcinomas) exhibiting at least three of the Tabar and Dean criteria. The authors were unable to differentiate between the mammographic appearances of the radial scars and the cancers.…”
Section: Discussionmentioning
confidence: 99%
“…12,[15][16][17][18][19] The literature presents a confused picture with regard to the association of carcinoma with radial scar, with the incidence of associated breast carcinoma varying from 0% to 43%. 19,20,22,24,25,29,[31][32][33][34][35] The reported differences in the association of breast carcinoma with radial scars are difficult to reconcile. Many studies are limited by small numbers, the retrospective nature of the analysis, and sometimes by a selection bias of patients likely to be at risk of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…30 Some studies reviewing radial scars have reported a high rate of association with DCIS and invasive carcinoma (up to 43% in one series). 18,19,29,30,33,34 These series derived patients from selected sources, such as a surgical service of a cancer hospital and other tertiary referral centers, where patients are more likely to be at risk of breast carcinoma. They were mostly case series, and not population-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, larger radial scars are being detected with increasing frequency in women who undergo mammographic screening. The morphologic similarity of radial scars to cancer [8][9][10][11][12] and the finding of carcinoma in some radial scars [13][14][15] have suggested that these lesions may represent an early phase in the development of certain types of breast cancer. Several studies have evaluated the frequency of radial scars in women with breast cancer, but with conflicting results.…”
Section: Discussionmentioning
confidence: 99%